Long-term results of the plastic correction of mitral insufficiency with the violation of the integrity of the chordal-papillary continium - О. О. Bolshak; V. I. Mnishenko; О. М. Trembovetska; V. М. Beshlyaga; I. V. Leoshko; V. V. Popov (Ukrainian Journal of Cardiovascular Surgery, 2017)
The article is devoted to the analysis of the long-term results of plastic correction of mitral insufficiency in case of violation of the integrity of the chordo-papillary apparatus. 201 patients were included in the analyzed group. The operations were consistently executed for the period from 01.01.2006 to 31.12.2015 yy. in different departments of the National Amosov’s Institute of Cardiovascular Surgery of National Academy of Medical Sciences of Ukraine. In 67.7%, in addition to the mitral valve, accompanying surgical procedures were performed. In 89% of cases, only the posterior valve leaflet was affected. Isolated abruption of chords and papillary muscles of P2 segment was observed in 66.5% of cases. Support rings and semirings were used in 88.5% of patients, suture annuloplasty was perfomed in 7.5% of patients, annuloplasty was not performed in 4.0%. Long-term results were studied in 95.5% of patients. The average follow-up period was 6.5±2.8 years. In 79.2% of cases, good and satisfactory results were obtained. 9 patients (4.7%) died in the long-term. Unsatisfactory results were obtained in 16.6% of patients. In 5 patients (2.6%), the mitral valve was re-operated in the long-term period. In the absence of any annuloplasty, unsatisfactory results and deaths in long-term periods were obtained in 50% of patients (4 of 8), with the use of support rings and semirings in 19.7% of cases, with the use of suture annuloplasty in 13.3% of cases. The most favorable long-term results were obtained with the initial lesion of only the posterior leaflet of the mitral valve (81.5% of good and satisfactory results versus 61.1% with lesion of the anterior leaflet only). Thromboembolic complication in the long-term period was recorded in 1 patient (0.5%). The mitral valve repair has proved to be a reliable way of correcting this pathology.